ANALISIS METODE PERSEDIAAN TEPAT WAKTU (JUST IN TIME) SEBAGAI DASAR PENGENDALIAN PERSEDIAAN BAHAN BAKU PEMBANTU ( STUDI PADA PG. LESTARI NGANJUK) - SHOLEHUDIN, MUHAMMAD (Jurnal Akuntansi AKUNESA, 2017)
The purpose of this study was to determine the auxiliary raw material inventory control by PG. Lestari Nganjuk using Just In Time. This study is descriptive research with qualitative approach. Analysis of the data used in this research using Just In Time. This study finds that by using Just In Time method, company could save cost since the company is not necessary to bear storage cost of the auxiliary raw materials. Therefore, with Just In Time method, this study finds total cost differences in 2013-2015 which consists of total saving for phosphate auxiliary raw materials, kapur pabrikasi and sulfur.  Based on the results of the analysis conducted in order to minimize the total cost incurred by the company each year should be PG. Lestari Nganjuk apply Just In Time method in determining quantity of optimal raw material auxiliary purchasing.